2020
DOI: 10.30699/ajnmc.27.6.424
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bristol's tool in lactation Counseling and its Impact on the Breastfeeding Status in Primiparous Mothers Undergone Cesarean Section

Abstract: Mothers of cesarean section need more support for breastfeeding. The purpose of this study was to use Bristol's tool for lactation counseling on the breastfeeding status in mothers undergone Cesarean section. Methods: In this quasi-experimental study,80 primiparous women after cesarean section In Fatemieh Hospital of Hamedan in year 2018 were selected by available sampling method and assigned to two groups of test (pairs) and control (individual days) (40 persons per group). In two groups, the researcher revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In general, the interventions of the reviewed studies were classified as follows: - Counseling interventions: including cognitive-behavioral counseling ( 27 ). breast-feeding counseling ( 28 ), participative counseling approach on improving BSE ( 29 ), incorporation of stress management counseling ( 17 , 30 ), in-home supportive counselling ( 31 – 32 ) and dialectical behavior therapy (DBT) ( 25 ). - Educational interventions, including educational packages ( 33 ), training sessions at home with educational pamphlet ( 34 ), and face-to-face training, and training by role-playing ( 35 ), interventions were done via SMS and text messages about infant care and maternal mental health ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the interventions of the reviewed studies were classified as follows: - Counseling interventions: including cognitive-behavioral counseling ( 27 ). breast-feeding counseling ( 28 ), participative counseling approach on improving BSE ( 29 ), incorporation of stress management counseling ( 17 , 30 ), in-home supportive counselling ( 31 – 32 ) and dialectical behavior therapy (DBT) ( 25 ). - Educational interventions, including educational packages ( 33 ), training sessions at home with educational pamphlet ( 34 ), and face-to-face training, and training by role-playing ( 35 ), interventions were done via SMS and text messages about infant care and maternal mental health ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…- Counseling interventions: including cognitive-behavioral counseling ( 27 ). breast-feeding counseling ( 28 ), participative counseling approach on improving BSE ( 29 ), incorporation of stress management counseling ( 17 , 30 ), in-home supportive counselling ( 31 – 32 ) and dialectical behavior therapy (DBT) ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a meta-analysis study showed that theoretical breast-feeding education provided to pregnant women in a health center contributed positively to breastfeeding self-efficacy [34]. In addition to self-efficacy, breastfeeding counseling was reported to have a positive effect on breastfeeding behavior itself in one of the studies [35]. Providing breastfeeding counseling can be expected to have a positive effect on breastfeeding behavior, because it is a skill that requires acquisition [36] and breastfeeding counseling involves the hands-on practice of breastfeeding skills, assisting mothers in holding their infants correctly, managing common breast issues, such as nipple injuries, engorgement and mastitis [37].…”
Section: Discussionmentioning
confidence: 96%
“…Many research studies examined the effect of verbal education and individual counseling (19,20,23,27,42,43). Although one study used telephone support as the primary educational method for interventions, it was often included as a supplementary mode of delivery for educational information on breastfeeding (38). A positive relationship may exist between prenatal class attendance and breastfeeding (27,38).…”
Section: Discussionmentioning
confidence: 99%
“…Although one study used telephone support as the primary educational method for interventions, it was often included as a supplementary mode of delivery for educational information on breastfeeding (38). A positive relationship may exist between prenatal class attendance and breastfeeding (27,38). Many studies in the literature that examined the effect of breastfeeding education delivered in the prenatal period included group educational sessions.…”
Section: Discussionmentioning
confidence: 99%